Penerapan Asas Peradilan: Studi Kekurangan Hakim Di Pengadilan Agama Sentani-Papua - Amri, Amri (Faculty of Law Hang Tuah University, 2023)
The conditions that occurred in the Sentani–Papua Religious Court experienced the limitations of a judge who had a dual role as a mediator. of course, these conditions will have an impact on the application of the Principle of Justice which is fast, simple and low cost in the Sentani-Papua Religious Court. So this study aims to find out how the strategy carried out by the Sentani Religious Court in implementing the Judicial Principle with these conditions and sites. This research was conducted through interviews, observations and documentation. If we look at this research shown to an institution, this research is a field study based on Qualitative research. The results showed that the Sentani Religious Court in implementing the Judicial Principle (Fast, Simple, Low Cost) with existing limitations has several strategies for how the judicial principle must be enforced. The strategy carried out is first, the application of the single judge in Examining, Adjudicating, advocating and deciding. Second, the Placement of Legal Aid Institutions to Manage Legal Aid Posts located in the Sentani Religious Court. Third, the acceptance of certified non-judge mediators so that judges in the Sentani Religious court no longer need to concurrently serve as mediators.